A novel biotechnology based on periphytic biofilms with N-acyl-homoserine-lactones stimulation and lanthanum loading for phosphorus recovery. (March 2022) - Xu, Ying; Kerr, Philip G.; Dolfing, Jan; Rittmann, Bruce E.; Wu, Yonghong
Graphical abstract: Highlights: La loading to periphytic biofilm was mainly based on ligand exchange reactions. La-loading achieved rapid initial P-entrapment. AHLs stimulated periphytic biofilm growth and formation. AHLs-stimulation enhanced steady and efficient P-entrapment. Enhanced EPS production stimulated by AHLs can protect cells against La exposure. Abstract: This study presents an approach for developing periphytic biofilm with N-acyl-homoserine-lactones (AHLs) stimulation and lanthanum (La, a rare earth element) loading, to achieve highly efficient and stable phosphorus (P) recovery from wastewater. AHLs stimulated biofilm growth and formation, also improved stable P entrapment by enhancing extracellular polymeric substance (EPS) production and optimizing P-entrapment bacterial communities. Periphytic biofilms loading La is based on ligand exchanges, and La loading achieved initial rapid P entrapment by surface adsorption. The combination of AHLs stimulation and La loading achieved 99.0% P entrapment. Interestingly, the enhanced EPS production stimulated by AHLs protected biofilms against La. Moreover, a method for P and La separately recovery from biofilms was developed, achieving 89–96% of P and 88–93% of La recovery. This study offers a promising biotechnology to reuse La from La-rich wastewater and recover P by biofilm doped with La, which results in a win–win situation for resource sustainability.